Real-world efficacy and tolerability of fremanezumab in adults with chronic migraine: a 3-month, single-center, prospective, observational study - Cullum, Christopher Kjaer; Chaudhry, Basit Ali; Do, Thien Phu; Amin, Faisal Mohammad (Frontiers in Neurology, 2023)
Background Following the promising pre-marketing placebo-controlled randomized clinical trials of fremanezumab, post-marketing studies are necessary to verify efficacy and tolerability in various real-world settings. The present study assessed real-world efficacy and safety of fremanezumab. Methods A 3-month, single-center, prospective, observation study of adults with chronic migraine who were treated with monthly subcutaneous injections of 225 mg fremanezumab in Denmark. The primary outcome was defined as proportion of patients who achieved ≥30% reduction in monthly migraine days (MMDs) from baseline to weeks 9–12. Among secondary outcomes were ≥50 and ≥75% responder rates and the proportion of patients reporting adverse events. Results A total of 91 patients with chronic migraine were enrolled and received at least one dose of fremanezumab of whom 89 patients (98%) completed the 3-months treatment period. At baseline, the mean (SD) number of monthly headache days was 24.3 ± 5.8 and mean number of MMDs was 18.5 ± 7.4. The number of patients who achieved ≥30% reduction in MMDs from baseline to weeks 9–12 was 58 (65%), while 45 (51%) and 21 (24%) had ≥50 and 75% reduction in MMD, respectively. Twenty-one patients (23%) reported adverse event, in which the most common were constipation (4.4%), fatigue (4.4%) and dizziness (3.3%). No serious adverse events were reported. Conclusion In adult chronic migraine patients with previous failure of conventional oral migraine preventives, fremanezumab was found to be effective and well-tolerated.